2015
DOI: 10.1016/j.epsl.2015.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the CO 2 budget and H 2 O–CO 2 systematics in subduction-zone magmas through the experimental hydration of melt inclusions in olivine at high H 2 O pressure

Abstract: HIGHLIGHTS:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
17

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 50 publications
5
64
0
17
Order By: Relevance
“…Unfortunately, the literature is replete with measurements of CO 2 in melt inclusions compromised by degassing or bubble formation. After bubble reconstruction, arc melt inclusions may contain thousands of parts per million of CO 2 82,83 , but there is no guarantee that these melts did not lose CO 2 by degassing before inclusion formation. Thus, a major outstanding challenge is to determine the CO 2 concentration of primary arc magmas (Box 4).…”
Section: Carbon Returned: Volcanic Gasmentioning
confidence: 99%
“…Unfortunately, the literature is replete with measurements of CO 2 in melt inclusions compromised by degassing or bubble formation. After bubble reconstruction, arc melt inclusions may contain thousands of parts per million of CO 2 82,83 , but there is no guarantee that these melts did not lose CO 2 by degassing before inclusion formation. Thus, a major outstanding challenge is to determine the CO 2 concentration of primary arc magmas (Box 4).…”
Section: Carbon Returned: Volcanic Gasmentioning
confidence: 99%
“…Quantification of outputs continues to evolve because of the difficulty in measuring CO 2 outgassing. Early estimates indicated that up to 97% of the CO 2 in arc volcanic rocks was derived from the subducting oceanic slab [Hilton et al, 2002], while more recently high pressure experiments have favored~80% as being more typical [Mironov et al, 2015], consistent values derived from measuring CO 2 and 3 He ratios in magmatic volatiles [Marty and Tolstikhin, 1998].…”
Section: Introductionmentioning
confidence: 98%
“…Another approach involved experimental heating of olivine-hosted inclusions, with the aim of rehomogenizing the inclusion system to a silicate melt which can then be quenched to recover the CO 2 content at the time of entrapment [Cervantes and Wallace, 2003;Wallace et al, 2015;Hudgins et al, 2015]. However, it is known that the temperature of homogenization in such experiments is significantly higher than the likely entrapment temperature, a mismatch which will cause the reconstructed relationship between CO 2 and major elements contents of the inclusion system to deviate from the natural case [Sobolev and Danyushevsky, 1994;Massare et al, 2002;Wallace et al, 2015;Mironov et al, 2015;Schiavi et al, 2016].…”
Section: Introductionmentioning
confidence: 99%